STRATEGI LATIHAN BEBAN DALAM MENINGKATKAN TEKNIK RENANG GAYA DADA PADA ATLET PEMULA - Nurhayati Simatupang; Rasika Nur Syabila; Rizky Pazari; Moses Parlindungan Gulo; Aldo Marasi Sihombing (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of dry-land training strategies on improving the breaststroke technique in beginner swimmers. The research method used was a literature review with a qualitative descriptive approach, involving the analysis of various sources of literature, including books, scientific journals, and relevant previous research findings. The results of the study indicate that weight training plays a crucial role in enhancing lower-body and upper-body muscle strength, which supports the kicking and arm-pull movements in breaststroke. Additionally, weight training helps improve movement coordination, body stability, and movement efficiency in the water, thereby enhancing swimming technique and minimizing errors. A training strategy conducted gradually with light to moderate intensity is considered effective and safe for beginner athletes. Exercises such as squats, pull exercises, and core training have been proven to support the development of functional strength appropriate for the movement requirements of breaststroke. Thus weight training can be used as an effective training strategy to improve breaststroke technique in beginner athletes.